Immunogenicity of the 9-valent HPV Vaccine Using 2-Dose Regimens in Girls and Boys Vs A 3-Dose Regimen in Women - Ole Erik Iversen (2018)
IMPORTANCE Human papillomavirus (HPV) infections cause anogenital cancers and warts. The 9-valent HPV vaccine provides protection against 7 high-risk types of HPV responsible for 90% of cervical cancers and 2 other HPV types accounting for 90% of genital warts. OBJECTIVE To determine whether HPV type-specific antibody responseswould be noninferior among girls and boys aged 9 to 14 years after receiving 2 doses of the 9-valent HPV vaccine compared with adolescent girls and youngwomen aged 16 to 26 years receiving 3 doses. DESIGN, SETTING, AND PARTICIPANTS Open-label, noninferiority, immunogenicity trial conducted at 52 ambulatory care sites in 15 countries. The study was initiated on December 16, 2013, with the last participant visit for this report on June 19, 2015. Five cohorts were enrolled: (1) girls aged 9 to 14 years to receive 2 doses 6 months apart (n = 301); (2) boys aged 9 to 14 years to receive 2 doses 6 months apart (n = 301); (3) girls and boys aged 9 to 14 years to receive 2 doses 12 months apart (n = 301); (4) girls aged 9 to 14 years to receive 3 doses over 6 months (n = 301); and (5) a control group of adolescent girls and young women aged 16 to 26 years to receive 3 doses over 6 months (n = 314). INTERVENTIONS Two doses of the 9-valent HPV vaccine administered 6 or 12 months apart or 3 doses administered over 6 months. MAIN OUTCOMES AND MEASURES The primary end pointwas prespecified as the antibody response against each HPV type assessed 1 month after the last dose using a competitive immunoassay. Each of the three 2-dose regimens was compared with the standard 3-dose schedule in adolescent girls and young women using a noninferiority margin of 0.67 for the ratio of the antibody geometric mean titers. RESULTS Of the 1518 participants (753 girls [mean age, 11.4 years]; 451 boys [mean age, 11.5 years]; and 314 adolescent girls and young women [mean age, 21.0 years]), 1474 completed the study and data from 1377 were analyzed. At 4 weeks after the last dose, HPV antibody responses in girls and boys given 2 doses were noninferior to HPV antibody responses in adolescent girls and young women given 3 doses (P < .001 for each HPV type). Compared with adolescent girls and young women who received 3 doses over 6 months, the 1-sided 97.5%CIs for the ratio of HPV antibody geometric mean titers at 1 month after the last dose across the 9 HPV subtypes ranged from 1.36 to ∞ to 2.50 to ∞ for girls who received 2 doses 6 months apart; from 1.37 to ∞ to 2.55 to ∞ for boys who received 2 doses 6 months apart; and from 1.61 to ∞ to 5.36 to ∞ for girls and boys who received 2 doses 12 months apart. CONCLUSIONS AND RELEVANCE Among girls and boys aged 9 to 14 years receiving 2-dose regimens of a 9-valent HPV vaccine separated by 6 or 12 months, immunogenicity 4 weeks after the last dose was noninferior to a 3-dose regimen in a cohort of adolescent girls and young women. Further research is needed to assess persistence of antibody responses and effects on clinical outcomes.